Echinococcus granulosus sensu lato GENOTYPES IN DOMESTIC LIVESTOCK AND HUMANS IN GOLESTAN PROVINCE, IRAN - SHARBATKHORI, Mitra (Rev Inst Med Trop Sao Paulo, 2016)
Cystic echinococcosis (CE) is a globally parasitic zoonosis caused by larval stages of Echinococcus granulosus. This study investigated E. granulosus genotypes isolated from livestock and humans in the Golestan province, northern Iran, southeast of the Caspian sea, using partial sequencing data of the cytochrome c oxidase subunit 1 (cox1) and NADH dehydrogenase 1 (nad1) mitochondrial genes. Seventy E. granulosus isolates were collected from animals in slaughterhouses: 18 isolates from sheep, 40 from cattle, nine from camels, two from buffaloes and one from a goat, along with four human isolates (formalin-fixed, paraffin-embedded tissues) from CE patients of provincial hospitals. All isolates were successfully analysed by PCR amplification and sequencing. The sequence analysis found four E. granulosus genotypes among the 74 CE isolates: G1 (78.3%), G2 (2.7%), G3 (15%) and G6 (4%). The G1-G3 complex genotype was found in all of the sheep, goat, cattle and buffalo isolates. Among the nine camel isolates, the frequency of G1-G3 and G6 genotypes were 66.7% and 33.3%, respectively. All four human CE isolates belonged to E. granulosus sensu stricto. This study reports the first occurrence of the G2 genotype in cattle from Iran and confirms the previously reported G3 genotype in camels in the same country.